Sensitive Magnetic Field Sensor Based on Compensated Double Pick Up Coil - Purnama, Budi; Suharyana, Suharyana; Sutomo, Artono Dwijo (IPTEK The Journal for Technology and Science, 2012)
Sensitive magnetic field sensor based on compensated double pick up coil has been developed. In order to confirm sensitifity of modified design, experiment carried out in two steps. Firstly, sensitify of conventional design is clarified. Here pick up coil as an active sensor and solenoid as an exitation coil is separately made. Secondly, modified sensor of integrated configuration is developed. Here for both active flux gate sensor and the exitation coil is made in same one core magnetic. Ferrite and standar foil soft magnetic is utilized in this experiment. In attention, frequency of 50 Hz is used for the whole experimens. A result showed that sensitvity of the integrated configuration sensor is much larger than conventional one. Then, power consume of the integrated flux gate sensor is much lower than conventional. Finally, a range measurement of the integrated configuration sensor can be realized less than 20 ïT which potential may perhaps sense a change of natural local magnetic field.